HLA class II antigen (DRB1 and DQB1) and rheumatoid arthritis in a Tunisian population: Relation to autoantibodies and disease severity - Boussaid, Soumaya; Tbini, Houssem; Makhlouf, Yasmine; Hassayoun, Maroua; Lagha, Aouatef; Ghazouani, Ezzeddine; Kochbati, Samir; Rekik, Sonia (Trends in Immunotherapy, 2023)
We aimed to evaluate the association of HLA DRB1 and DQB1 alleles with rheumatoid arthritis (RA), and to investigate their relationship with anti-citrullinated peptide antibodies (ACPA) and RA severity. We performed a case-control study of 81 RA patients compared with 100 healthy controls. Sociodemographic data, disease activity scores, functional impact, structural damage, ACPA, rheumatoid factor (RF), and HLA DRB1 and DQB1 alleles were determined. Forty-six patients expressed HLA DRB1, predominantly DRB1*04. These alleles were more frequent in RA patients than in controls. DRB1*04:05 was the most associated allele with RA susceptibility, 54.5% of RF-positive patients expressed DRB1*04:05 with a significant correlation. Similarly, a highly significant association with DRB1*15:01 and RF positivity was found. DRB1*01:01, 04:05, 11:01, and 15:01 were associated with the presence of ACPA. Patients with DRB1 alleles had more extraarticular manifestations (EAM). Multivariate analysis concluded that DRB1*04:05 was only associated with ACPA positivity. Regarding DQB1, DQB1*03:02 was the most associated with RA. DQB1*02:01, 03:01, 03:02, 05:01, and 06:01 were associated with RF-positive RA. DQB1*06:01 was associated with ACPA. Only HLA DQB1*02:01 and 06:01 were associated with the presence of EAM. DAS28 was reduced in the presence of DQB1. HAQ > 0.5 were correlated with DQB1 alleles. In addition, there was more structural damage in RA encoding for DQB1. In linear regression, DQB1*06:01 were associated with RF positivity, but there was no association with the other parameters. Our study confirmed that DRB1 and DQB1 expression was significantly associated with ACPA, increased HAQ, increased sharp score, and the presence of EAM.